The role of communication in the management and leadership of a secondary school in Namibia - Kaura, Unjee M (Rhodes University, Faculty of Education, Department of Education, 2005)
Communication is a complex phenomenon, widely regarded as the lifeblood of every organisation, and ironically one of the least researched areas, at least in the field of leadership and management in an educational context. The paucity of literature in this field is evidence of this. This study is an attempt to explore and gain understanding of teachers' experiences and perceptions of the role and functions of communication within an educational organisation, in this case a secondary school in Namibia. The study is an interpretive case study, and employed questionnaires and interviews to gather data from selected participants at the site of research. The findings of the study highlight the dual role of communication as a functioning mechanism as well as a social or binding factor. The role of communication emerges as an essential element in the democratic functioning of the school. It is through communication that democratic practice is achieved as a vehicle for involvement in decision-making, sharing, teamwork, and as a medium for leadership leading to empowerment, human development and organisational development, bringing about change through the sharing of vision. Both formal and informal communication are shown to be functional to the institution. Some of the challenges that have emerged are the dangers of careless and malicious 'badmouthing' in informal communication, the persistence of some degree of top-down communication, and the challenges of communication in multi-cultural settings. The study highlights the need for strategies to improve communication, such as workshops on interpersonal communication.
Keywords: Uncatalogued